2010
DOI: 10.1002/qua.22797
|View full text |Cite
|
Sign up to set email alerts
|

Comparative semiempirical and DFT study of styrylnaphthalenes and styrylquinolines and their photocyclization products

Abstract: Semiempirical molecular orbital (PM3, PM6, and RM1) and density functional theory (DFT) (B3LYP/6-31G*) studies are carried out for 1-and 2-styrylnaphthalenes and their aza-derivatives-2-and 4-styrylquinolines. Relative stabilities of three isomeric forms: E-and Z-isomers and the closed-ring dihydrocyclophotoproduct (derivative of dihydrophenanthrene) are calculated. Compared to PM3, PM6 and especially RM1 understate heats of formation; in some cases, PM6 and RM1 even place Z-isomer in energy below E-isomer. PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Comparison of different semiempirical methods − PM3, PM5, PM6, and RM1 – in calculations of diarylethylenes28, 29 showed that comparatively recently developed methods PM5, PM6, and RM1 overestimated relative stability of Z ‐isomers (underestimated heat of isomerization reaction), and in some cases even placed Z ‐isomers below E ‐isomers on the energy scale. Being in general clearly superior,30 as applied to calculation on diarylethylenes, the new parametric methods proved to be somewhat worse than PM3 31.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison of different semiempirical methods − PM3, PM5, PM6, and RM1 – in calculations of diarylethylenes28, 29 showed that comparatively recently developed methods PM5, PM6, and RM1 overestimated relative stability of Z ‐isomers (underestimated heat of isomerization reaction), and in some cases even placed Z ‐isomers below E ‐isomers on the energy scale. Being in general clearly superior,30 as applied to calculation on diarylethylenes, the new parametric methods proved to be somewhat worse than PM3 31.…”
Section: Methodsmentioning
confidence: 99%
“…In order to estimate the effect of the introduced structural modifications on the conformational properties of the new TSPs, the former lead 1 was included in the analysis. Indeed, the conformational space of the first series of TSPs was explored by applying in vacuum semi-empirical PM6 [ 16 ] calculations [ 11 ] while, in the present study, we performed density functional theory (DFT) [ 17 ] calculations and used the conductor-like polarizable continuum model (C-PCM) [ 18 ] to mimic an aqueous environment.…”
Section: Resultsmentioning
confidence: 99%
“…clization reaction of 2-styrylquinoline (in S 0 state) [30,31]. The closed-ring compounds (DHPs), if formed in the excited state, due to thermal instability decompose rapidly with ring opening in the ground state that prevents their observation in steady-state photolysis.…”
Section: Photonics Of 2-styrylquinolinementioning
confidence: 99%